1989
DOI: 10.1002/ajmg.1320330102
|View full text |Cite
|
Sign up to set email alerts
|

Wisconsin consanguinity studies. II: Familial adenocarcinomatosis

Abstract: Predisposition to carcinoma in certain families has been recognized as an autosomal dominant trait. We describe a large pedigree (over 1,000 persons) including ten consanguineous unions with inbreeding coefficients from 0.02 to 0.17. Persons of consanguineous parentage accounted for 16 of 18 cases of adenocarcinoma (most of which were colorectal). Three women with breast cancer were relatives but not of consanguineous parentage. Only six of 36 persons with a malignancy of any kind were unrelated spouses, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Similar observations were published in a Pakistani study where cancer patients, on average, have a higher coefficient of inbreeding as compared with the general population. 7 Another study demonstrated that 94% of the subjects with reported adenocarcinomas (mostly colorectal) originated from a consanguineous population of descendants of an Italian immigrant group in Wisconsin, 6 suggesting an explanation for increased cancer incidence with higher degree of inbreeding. Thus, an explanation for increased cancer risk based on the frequency of homozygous regions and consanguinity has formed the basis of a potentially new model of cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were published in a Pakistani study where cancer patients, on average, have a higher coefficient of inbreeding as compared with the general population. 7 Another study demonstrated that 94% of the subjects with reported adenocarcinomas (mostly colorectal) originated from a consanguineous population of descendants of an Italian immigrant group in Wisconsin, 6 suggesting an explanation for increased cancer incidence with higher degree of inbreeding. Thus, an explanation for increased cancer risk based on the frequency of homozygous regions and consanguinity has formed the basis of a potentially new model of cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the genetic factors underlying familial CRC syndromes have been delineated, little is known about the genetic risk determinants of CRC in the general population. Current clues that suggest the involvement of recessively acting genes are based on the data associated with consanguinity and from populations that are characterized by a high degree of inbreeding [3][4][5][6][7][8] as well as from studies in animals. 9 The Saudi population is known for having relative genetic homogeneity due to particular demographic, historic, and tribal characteristics and is known for high consanguinity.…”
Section: Introductionmentioning
confidence: 99%
“…20 Of great interest, forms of constitutional LOH have been implicated in predisposition to malignancies, a fact best illustrated in inbred ethnic populations. [21][22][23][24] Comparisons of germline SNP-A data of 74 colorectal cancer patients identified that the percentage of those with autozygous segments of 4 Mb or more is at least twice as high as in control groups. 25 However, specific locations and disease associations, including their contribution to disease risk, are currently not well defined.…”
Section: Pathogenesis Of Cn-lohmentioning
confidence: 99%
“…Clues that tumor susceptibility may have a recessive basis come from reports of an increased incidence associated with consanguinity and in populations characterized by a high degree of inbreeding. [4][5][6][7][8][9] Further evidence for the role of homozygosity in cancer predisposition is provided by experimental animal inbreeding (eg, backcrossing mice) increasing tumor incidence. 10 Specific situations of homozygosity have also been directly associated with cancer, such as uniparental disomy through altered imprinting.…”
Section: Introductionmentioning
confidence: 99%